Design and assessment of an energy self-supply process producing tetraethyl orthosilicate using rice husk. (January 2022) - T. H. Nguyen, Thuy; Fukaya, Norihisa; Sato, Kazuhiko; Choi, Jun-Chul; Kataoka, Sho
Graphical abstract: Highlights: An energy self-supply process producing TEOS using rice husk is designed. Total production cost and cradle-to-gate CO2 emissions are thoroughly evaluated. Feasibility is examined by comparing with process using conventional raw materials. Large CO2 reduction is achieved, as all energy demands can be internally supplied. High economic benefit is gained when renewable electricity is cogenerated and sold. Abstract: Combusting rice husk (RH) generates energy and rice husk ash (RHA) containing high amount of silica. Recent studies showed RHA can directly react with ethanol for producing tetraethyl orthosilicate (TEOS), an important substance for different industries. Nevertheless, this process requires an intensive energy supply. This study aims to design and evaluate an energy self-supply process producing TEOS using RH for feasibility. A process simulator was used to design the target process. The simulation results revealed that RH combustion can completely meet the RHA and high energy demands of TEOS production. The economic and environmental benefits were thoroughly evaluated and compared with processes using conventional raw materials (i.e., Simg and silica). The evaluation results showed that using RH for TEOS production could reduce CO2 emissions substantially. Large economic benefit was gained when renewable electricity was co-generated and sold to the power grid as a surplus.